PENGGUNAAN QUIZIZZ DALAM PENILAIAN HARIAN UNTUK MENINGKATKAN HASIL BELAJAR IPS - MURNIATUN MURNIATUN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The Assesment of learning outcomes is an important component in learning activities. One of the efforts to improve the quality of learning can be achieved through improving the quality of the assessment system. The instruments to achieve of learning outcomes should notice to the development and ability of every single students. Mostly the teachers still using regular written test by using book right until now. This case provokes the students’ learning habit become less efective that lead to the low of the learning outcomes. By using Quiziz can improve the students’ motivation and the learning outcomes. The beneficial of using Quiziz are easier to use and generate the score automatically. This research is aiming to apply Quiziz on daily test and improving the learning outcomes for social students. The research is conducted at Junior High School Number 3 Lais, District of Musi, Banyuasin, Sumatera Selatan and the subject of this research are the students of IX-2 which amount to 34 people. This research conducted with two cycles. The source of the datas in this research are coming from the quantitative of daily test, every final result of each cycle. The result of this research showed that in the first cycle of daily test using regular multiple choice questions on the paper of the 34 students, only 16 students were passed with the percentation of 47%. In the second cycle the daily test using Quiziz of the 34 students, there were 29 students passed with the percentation of 85,29%. There was significant increase on the result of the daily test for 38,29%. This result proves that using Quiziz for daily test can improving the score of daily test for social students on the sub subject of inter-space dependence is seen from the economic concept and its influence on population migration, transportation,social and economic institutions. ABSTRAKPenilaian hasil belajar merupakan komponen penting dalam kegiatan pembelajaran. Upaya peningkatan mutu pembelajaran salah satunya dapat ditempuh melalui peningkatan kualitas sistem penilaiannya. Instrumen pencapaian hasil belajar harus memperhatikan perkembangan dan kemampuan siswa. Kebanyakan guru masih menggunakan penilaian berupa tes tertulis. Hal ini berakibat proses belajar menjadi kurang berkesan bagi siswa sehingga hasil belajar siswa menjadi rendah. Permainan Quizizz bisa menjadi motivasi belajar siswa dan meningkatkan hasil belajar. Penggunaannya mudah dan proses penilaiannya yang cepat karena tidak perlu mengoreksi secara manual.Penelitian ini bertujuan menerapkan penggunaan Quizizz dalam penilaian harian meningkatkan hasil belajar IPS. Penelitian ini dilakukan di SMP Negeri 3 Lais, Kabupaten Musi Banyuasin, Sumatera Selatan, Subjeknya siswa kelas IX.2 berjumlah 34 orang. Penelitian ini dilakukan dengan dua kali siklus. Sumber data pada penelitian ini adalah kuantitatifdari nilai harian yang diambil pada setiap akhir siklus. Hasil penelitian menunjukkan bahwa pada siklus 1 penilaian harian dengan menggunakan soal pilihan ganda, dari 34 peserta didik yang tuntas berjumlah 16 orang jika diprosentase sebesar 47%. Pada Siklus 2 Penilaian harian dengan menggunakan quizizz , peserta didik yang tuntas berjumlah 29 orang dengan prosentase ketuntasan sebesar 85,29%. Terjadi peningkatan hasil belajar sebanyak 38,29%. Penggunaan Aplikasi Quizizz pada penilaian Harian dapat meningkatkan hasil belajar IPS pada materi Ketergantungan antar ruang dilihat dari konsep ekonomi dan pengaruhnya terhadap migrasi penduduk, transportasi, lembaga sosial dan ekonomi